Structure of the Macrozoobenthos Community in Estuaria of Padang Pariaman Regency - Adnal Yeka; Abdul Razak; Eni Kamal; Isril Berd; Deni Sarianto; Athosra Athosra; Petrizal Petrizal (Science and Environmental Journal for Postgraduate, 2022)
This research was carried out in rivers and estuaries in the Batang Naras River, Padang Pariaman Regency, West Sumatra. The river is often used by residents for pond irrigation and ice factory cooling machines. This activity will indirectly affect the biota in rivers and estuaries. Macrozoobenthos is one of the biological aspects that play an important role in assessing the quality of water. The purpose of this study was to determine the community structure of macrozoobenthos in the estuary of Batang Naras. The method used is a descriptive survey. Sampling was done by purposive sampling by setting up 3 research stations. Based on the research results found 2 phyla, namely Arthropoda and Mollusca, 3 classes namely Crustacea, Insects, and Gastropods, 6 orders, 11 families, and 12 genera. The highest benthic diversity index (H') was found at station I at 1.803 and the lowest was found at station III at 1.222. This zone belongs to lightly to moderately polluted waters and the dominance value is 0.5. Diversity and dominance show moderate values. The influence of industrial activities and aquaculture disturb the amount of benthos in the estuary.